MAKING PROCESS OF CERAMIC PANELS AND WALL PANELS IN CONTEMPORARY TURKISH CERAMIC ART - Bengütay HAYIRSEVER (Fırat University, 2020)
Culture, is the most important values of a society's past and history, that distinguishes it from other societies and makes it special.İn the branches where people are producers ,they contain all the values they add to life .Culture and human activities vary as the development of these activities changes from individual to social life and come up with different artistic creations.İn the historical process,ceramics entered the life of human beings as daily use items such as pots and pans.İn the next period,it has been a sought after material for beautifying people’s lives in the architectural field and adding aesthetic values. The rich heritage of all civilizations that lived in Anatolia has always been a source of inspiration for artists living in this land. Especially, Seljuk and Ottoman culture and art, which constitute the cornerstones of Anatolian architecture, have also been an inspiration to the artists who envisioning these values and reflected them in their works. Whit the history of the Republic,the importance and value attached to the arts and artists have increased.Domestic and international education scholarships have been given,ceramic factories,private workshops,art education institutions and art galleries have been opened.These factors were the beginning of important developments in contemporary Turkish ceramic art as well as in all branches of art. In contemporary Turkish ceramic art, of which, the rich Anatolian culture laid the foundations, the artists shaped ceramic wall panels with these cultural codes and their personal interpretations. Although the main ingredient of the produced works is clay; the artists, who are open to innovations and material diversity coming with technology, continued to produce in time by making use of these opportunities. In this research, ceramic materials used in historical architectural structures as tiles, brick works and wall panels in contemporary Turkish ceramic art are examined by giving examples from selected artists and their works.